Collaborative Governance in Combating Covid-19 in the Vuca Era in Cilacap Regency - Bambang Sulistyo Heri T; Diar Budi Utama; Rizky Robbyanica Paing (Indonesian Association for Public Administration (IAPA), 2022)
The development of strategic public administration issues is faced with the implementation of collaboration between elements or collaborative governance. A fascinating public issue to be studied in Indonesia is the problem of disaster management, considering that Indonesia is a highly disaster-prone area in the world. Lately, the disaster has focused on efforts to overcome Covid-19 which threatens people's lives and livelihoods. Cilacap Regency is the largest district in Central Java Province, with a disaster risk index with a high-risk category. Almost all disasters are in Cilacap Regency, such as floods, landslides, and the potential for a tsunami that has a high risk of happening in Cilacap because there are activities along the south coast. The researcher wants to achieve the research objective of seeking collaborative governance in dealing with Covid-19 in the VUCA era in Cilacap Regency. The research method used in this study is qualitative. Design study which conducted with use case study approach. The results of the study show that the collaborative governance process in dealing with the Covid-19 disaster in the VUCA era in Cilacap Regency provided a stimulus for each region in restoring conditions in aspects of life, both primary education, health, and financial services. In the face-to-face dialogue, the collaboration process has been carried out well through communication and coordination that can unite views. Indeed, disasters are a shared responsibility by synergizing between institutions. The role of communication between institutions is essential in learning mutual understanding and trust-building.